Quranic Verses in the Treatment of Bollution (Islamic Sciences Journal, 2023)
There are verses in the holy Qur’an that talk about the phenomenon of pollution as a hint and not explicitly. Yes, the verses did not explicitly mention pollution. Rather, they used the term corruption, which is more general than pollution Those holy verous stated the reasous behind that bad and dangerous phenomenon to the future of humanity . moreover, they explained the ways of prevention from this phenomenon. It is known that prevention is better than cure. After that, research seeks to address the phenomenon by finding appropriate basic solutions, or preventing its spread, in order to reduce its threat to global societies in this world.